Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41401-018-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium lithospermate B ameliorates microcirculation perfusion in rats by promoting vascular NO production via activating the PI3K/AKT pathway

Abstract: Microcirculation morphologically refers to the blood flow in vessels of less than 150 μm in diameter, including arterioles, capillaries and venules, which provides nutrients and removes metabolic byproducts within tissues. Microcirculation dysfunction is involved in the pathological progress of many diseases, such as obesity, hypertension, and insulin resistance. In this study we investigated the effects of magnesium lithospermate B (MLB), an active compound of the traditional Chinese medicine Slavia miltiorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…Its estrogenic activity may partly explain gender differences in disease susceptibility 33 . Studies have indicated the antiobesity effects of MLB involving the activation of Akt signaling and amelioration of endoplasmic reticulum stress, insulin resistance, and inflammation 16,34,35 . Despite the limited evidence, the current findings demonstrated an altered glucocorticoid receptor and PPARγ axis in BPA‐exposed rats and their reversal by MLB.…”
Section: Discussionmentioning
confidence: 50%
“…Its estrogenic activity may partly explain gender differences in disease susceptibility 33 . Studies have indicated the antiobesity effects of MLB involving the activation of Akt signaling and amelioration of endoplasmic reticulum stress, insulin resistance, and inflammation 16,34,35 . Despite the limited evidence, the current findings demonstrated an altered glucocorticoid receptor and PPARγ axis in BPA‐exposed rats and their reversal by MLB.…”
Section: Discussionmentioning
confidence: 50%
“…Cardiovascular disease is the principal cause of death and morbidity among people with diabetes, who have a two-to fourfold increased cardiovascular risk compared with adults without diabetes [1]. The cardiac microvasculature refers to vessels <150 μm in diameter, which provide nutrients and remove metabolic byproducts within the heart tissue [2]. Endothelial dysfunction is the initial factor and early pathological manifestation leading to diabetic microvascular diseases, which are believed to play important pathophysiological roles in the development of heart failure [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF is involved in both vasculogenesis and angiogenesis, which are critical for the development of the placenta. Previous study suggested that MLB can restore the microcirculation dysfunction via activating eNOS, and in turn, enhancing the vascular NO production [ 10 ]. In the present study, MLB also rescued the expressions of VEGF and NO, indicating the protective effect of MLB on the placental development.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium lithospermate B (MLB), an active component of the water-soluble fraction of Salvia miltiorrhiza , is noted for scavenging oxygen free radicals, protecting cell mitochondria, improving energy metabolism, and regulating gene expression. The protective effects of MLB on cerebral/hepatic/myocardial ischemia/reperfusion injury and renal injury together with vascular endothelial dysfunction via regulating inflammation and oxidative stress have been extensively demonstrated [ 10 14 ]. In another report, MLB was shown to prevent phenotypic transformation of pulmonary arteries with pulmonary hypertension and alleviate sodium-induced hypertension and renal failure in rats [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%